Po O. Východiska a inspirace pro výtvarnou tvorbu dětí v předškolním vzdělávání - Stadlerová, Hana (Masaryk University Press, 2021)
Title in English: Po O. The Possibilities and Inspiration for Art Creation of Children in Preschool Education This publication is aimed at improving the pedagogical practices of teachers in pre-school education. It offers information about fine art activities for pre-school aged children and explains the current objectives of pre-school education, which are implemented through integrative fine art activities. It defines the requirements for kindergarten teachers to create opportunities for teaching. The publication offers inspiring examples of creativity that can expand ideas about the creative possibilities of pre-school age children.